2020
DOI: 10.1111/jir.12739
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of people with intellectual disabilities during the 2017/2018 influenza epidemic in the Netherlands: potential implications for the COVID‐19 pandemic

Abstract: Background Data on the development of Covid‐19 among people with intellectual disabilities (IDs) are scarce and it is uncertain to what extent general population data applies to people with ID. To give an indication of possible implications, this study investigated excess mortality patterns during a previous influenza epidemic. Methods Using Dutch population and mortality registers, a historical cohort study was designed to compare mortality during the 2017–2018 influenza epidemic with mortality in the same pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…People with intellectual disabilities are a group at specific risk during the COVID‐19 coronavirus pandemic because of marked mental and physical health multimorbidity (Cuypers et al., 2020; Turk, Landes, Formica, & Goss, 2020). The social distancing and isolation measures implemented to manage the pandemic are known to impair mental health (Brooks et al., 2020; Torales, O'Higgins, Castaldelli‐Maia, & Ventriglio, 2020), and this burden is also likely to be greater for people with intellectual disabilities, because they have generally poorer coping abilities (Courtenay & Perera, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…People with intellectual disabilities are a group at specific risk during the COVID‐19 coronavirus pandemic because of marked mental and physical health multimorbidity (Cuypers et al., 2020; Turk, Landes, Formica, & Goss, 2020). The social distancing and isolation measures implemented to manage the pandemic are known to impair mental health (Brooks et al., 2020; Torales, O'Higgins, Castaldelli‐Maia, & Ventriglio, 2020), and this burden is also likely to be greater for people with intellectual disabilities, because they have generally poorer coping abilities (Courtenay & Perera, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a Dutch study of the 2017–2018 influenza season showed excess mortality related to influenza among people with intellectual disabilities to be three times higher than the general population. 12 People with intellectual disabilities may live in congregate settings where they have more close contact with the public putting them at higher risk for exposure. In addition, many people with intellectual disabilities have co-occurring chronic conditions which put them at higher risk for complications from influenza.…”
Section: Introductionmentioning
confidence: 99%
“…It has been broadly represented that, compared to adults, the prolonged pandemic and its restrictions may lead to short-term as well as long-term physical, psychosocial, educational and mental health implications for children and young people [13][14][15][16][17]. In particular, vulnerable paediatric populations (including those who are struggling with homelessness, pre-existing psychiatric conditions, developmental disabilities, special educational needs (SENs), substance use and abuse, and domestic violence) necessitate more support through their family and healthcare services because of their noticeable mental and physical health multimorbidity [18][19][20]. The ndings of research conducted during the pandemic on CYP with disabilities highlight drastic negative impacts of lockdown on varied aspects of their life, and di culties for their caregivers [21][22][23].…”
Section: Introductionmentioning
confidence: 99%